2018
DOI: 10.1080/20477724.2018.1446773
|View full text |Cite|
|
Sign up to set email alerts
|

Current progress of immunoinformatics approach harnessed for cellular- and antibody-dependent vaccine design

Abstract: Immunoinformatics plays a pivotal role in vaccine design, immunodiagnostic development, and antibody production. In the past, antibody design and vaccine development depended exclusively on immunological experiments which are relatively expensive and time-consuming. However, recent advances in the field of immunological bioinformatics have provided feasible tools which can be used to lessen the time and cost required for vaccine and antibody development. This approach allows the selection of immunogenic region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 79 publications
(79 reference statements)
0
56
0
Order By: Relevance
“…The most immunogenic epitope for the T and B cells involved in cell-mediated immunity was previously analyzed [18]. The main focus of the analysis was the MHC class I potential peptides using in silico analysis techniques [19,20]. In this study, the same techniques were applied to keep MHC classes I and II along with the world population coverage as our main focus.…”
Section: Introductionmentioning
confidence: 99%
“…The most immunogenic epitope for the T and B cells involved in cell-mediated immunity was previously analyzed [18]. The main focus of the analysis was the MHC class I potential peptides using in silico analysis techniques [19,20]. In this study, the same techniques were applied to keep MHC classes I and II along with the world population coverage as our main focus.…”
Section: Introductionmentioning
confidence: 99%
“…The main focus of the analysis was the MHC class-I potential peptides using in silico analysis techniques [19,20] . In this study, the same techniques were applied to keep MHC class I and II along with the world population coverage as our main focus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our results indicated that nine potential antigen epitopes were predicted in GRA12 by BCPREDS. Also, Bcepred's prediction accuracy for models based on different properties ranges from 52.92% to 57.53% and this server permits users to predict epitopes of B-cell using any of the physico-chemical properties (accessibility, hydrophilicity, polarity, flexibility/mobility, exposed surface, and turns) [39]. In addition, the online server of ABCpred predicts B-cell epitopes in an antigen sequence using ANN.…”
Section: Discussionmentioning
confidence: 99%